Phytohormones as regulators of heavy metal biosorption and toxicity in green alga Chlorella vulgaris (Chlorophyceae) - Piotrowska-Niczyporuk, Alicja; Bajguz, Andrzej; Zambrzycka, Elżbieta; Godlewska-Żyłkiewicz, Beata (Plant physiology and biochemistry, 2012)
The present study was undertaken to test the influence of exogenously applied phytohormones: auxins (IAA, IBA, NAA, PAA), cytokinins (BA, CPPU, DPU, 2iP, Kin, TDZ, Z), gibberellin (GA3), jasmonic acid (JA) as well as polyamine - spermidine (Spd) upon the growth and metabolism of green microalga Chlorella vulgaris (Chlorophyceae) exposed to heavy metal (Cd, Cu, Pb) stress. The inhibitory effect of heavy metals on algal growth, metabolite accumulation and enzymatic as well as non-enzymatic antioxidant system was arranged in the following order: Cd > Pb > Cu. Exogenously applied phytohormones modify the phytotoxicity of heavy metals. Auxins, cytokinins, gibberellin and spermidine (Spd) can alleviate stress symptoms by inhibiting heavy metal biosorption, restoring algal growth and primary metabolite level. Moreover, these phytohormones and polyamine stimulate antioxidant enzymes’ (superoxide dismutase, ascorbate peroxidase, catalase) activities and ascorbate as well as glutathione accumulation by producing increased antioxidant capacity in cells growing under abiotic stress. Increased activity of antioxidant enzymes reduced oxidative stress expressed by lipid peroxidation and hydrogen peroxide level. In contrast JA enhanced heavy metal toxicity leading to increase in metal biosorption and ROS generation. The decrease in cell number, chlorophylls, carotenoids, monosaccharides, soluble proteins, ascorbate and glutathione content as well as antioxidant enzyme activity was also obtained in response to JA and heavy metals. Determining the stress markers (lipid peroxidation, hydrogen peroxide) and antioxidants’ level as well as antioxidant enzyme activity in cells is important for understanding the metal-specific mechanisms of toxicity and that these associated novel endpoints may be useful metrics for accurately predicting toxicity. The data suggest that phytohormones and polyamine play an important role in the C. vulgaris responding to abiotic stressor and algal adaptation ability to metal contamination of aquatic environment. Auxins, cytokinins, gibberellin, jasmonic acid and spermidine can regulate heavy metal (Cd, Cu, Pb) biosorption and modify their toxic effect on Chlorella vulgaris growth, primary metabolite level and antioxidant system. [Display omitted] ► Heavy metals toxicity in C. vulgaris was arranged in the following order: Cd>Pb>Cu. ► Auxins, cytokinins, gibberellin and polyamine can alleviate heavy metals stress. ► Jasmonic acid enhanced harmful effect of heavy metals on algal cells.